AN ANALYSIS OF INTERPERSONAL FUNCTION IN MARIO TEGUH’S FACEBOOK STATUS - Melva Akmala; Busmin Gurning (State University of Medan, 2014)
ABSTRACT The objectives of the study were to describe the types of interpersonal function and the dominant type of interpersonal function used in Mario Teguh’s Facebook Status. This study was in descriptive quantitative method. This study dealt with the analysis of interpersonal function in Mario Teguh’s Facebook status. The data were the statuses of Mario Teguh and Mario Teguh’s Facebook account was used to take the statuses of his. The statuses were analyzed and classified based on the Speech Function and Mood as part of the interpersonal function. There were 200 Speech Function and 196 Moods as part of the interpersonal function in the selected statuses. The findings indicate that both all types of Speech Function and Moods are used in Mario Teguh’s Facebook Status. They were Statement, Question, Command, and Offer for the Speech Function, and Declarative, Interrogative, and Imperative for the Moods. It was found that the most dominant type of Speech Function is Statement (69.5%) and the most dominant type of Moods is Declarative (71%). It was seen that Mario Teguh mostly used Speech Function of Statement and Declarative Moods to share his ideas to the readers. Keywords: Speech Function, Moods.